Uji Efektivitas Antibakteri Ekstrak Temulawak (Curcuma Xanthorrhiza) terhadap Sampel Tuak - Dina Oktalia Putri; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Palm wine (tuak) is a traditional fermented beverage that is prone to microbial contamination, thus requiring natural alternatives with antibacterial properties. This study aimed to determine the effectiveness of Curcuma xanthorrhiza (temulawak) extract in inhibiting microbial growth in tuak samples. The method used was the disc diffusion test with three extract concentrations, 25%, 50%, and 100%. The tuak samples were first femented, serially diluted, and inoculated on Nutrient Agar (NA). Sterile paper discs soaked in each extract were placed on the medium surface and incubated at room temperature for 24 hours. The results showed no visible inhibition zones around the discs at any concentration tested. The conclusion of this study is that temulawak extract at concentrations of 25–100% did not demonstrate antibacterial activity against microorganisms in tuak samples. This study serves as a foundational evaluation of natural antibacterial agents and highlights the need for further optimization of extraction techniques or targeted testing on specific bacterial isolates.